Diagnostic Challenges and Innovations in Thoracic Endometriosis (TE) - Julia Bałoniak; Zofia Szymańska; Agnieszka Leszyńska; Zuzanna Bałoniak; Aleksandra Jonkisz; Gabriela Skurzyńska; Aleksandra Stremel; Michalina Doligalska (Quality in Sport)
Endometriosis is a condition characterized by the presence of endometrial tissue in ectopic locations outside the gynecological organs. Thoracic endometriosis (TE) is a rare and underdiagnosed condition characterized by the presence of endometrial-like tissue in the thoracic cavity, leading to cyclical respiratory symptoms. TE is often misdiagnosed or overlooked, primarily due to its nonspecific symptoms. Advancements in imaging techniques and biomarkers research are promising in improving the diagnosis of TE. High-resolution imaging modalities, such as high-resolution computed tomography (HRCT) and magnetic resonance imaging (MRI), provide detailed visualization of pleural and pulmonary lesions and leverage hormonal responsiveness for dynamic imaging during the menstrual cycle. The identification of novel biomarkers, such as cystatin C and circulating microRNAs, highlights the potential for non-invasive diagnostic tools that can stratify patients based on disease severity and guide personalized treatment strategies. Early diagnosis and treatment of thoracic endometriosis are crucial to prevent severe complications such as recurrent pneumothorax, pleural adhesions, and progressive lung damage. Timely intervention also reduces the burden of chronic pain and improves quality of life, enabling more effective management of this underdiagnosed condition. The aim of this paper is to explore current diagnostic possibilities for TE, particularly through the lens of advanced diagnostic innovations, and assess their potential to improve outcomes for patients with this complex condition.